Android apps development for image and video processing - Cheng, Nuo (Nanyang Technological University, 2023)
This project presents an Android-based image processing application that provides a user-friendly interface and a range of editing features to enhance image quality. The application allows users to capture images from their mobile device cameras or select images from the gallery. Users can then preview and edit images using filters and tools such as cropping, text and emoji addition, and filtering. The edited images can be saved to the device gallery or shared on social media platforms directly from the application.